Combinatorial synthesis of new fluorescent scaffolds using click chemistry. (5th January 2022) - Cleemann, Felix; Kum-Cheung, Wendy Loa; Karuso, Peter
Graphical abstract: Abstract: Azides and acetylenes are bio-orthogonal functional groups that can be readily coupled using copper(I)- or ruthenium(II)- catalyzed 1, 3-dipolar cycloaddition reactions. Using non-fluorescent aromatic azides and aromatic acetylenes, covering a range of electron rich and poor building blocks, the Huisgen cycloaddition afford 1, 4-disubstituted or 1, 5-disubstituted 1, 2, 3-triazoles. Using a combinatorial approach by running reaction in parallel in polypropylene 96-well plates we discovered several new fluorescent 1, 2, 3-triazoles scaffolds. These compounds show diverse interactions with biomolecules that could find applications in biology in, for example, fluorescence microscopy or biomolecule quantification.